2017
DOI: 10.1093/cid/cix167
|View full text |Cite|
|
Sign up to set email alerts
|

Antiretrovirals, Fractures, and Osteonecrosis in a Large International HIV Cohort

Abstract: In human immunodeficiency virus (HIV) infection, host factors, HIV-specific variables, and comorbidities contribute to risk of fractures and osteonecrosis. Exposure to TDF, but not other ARVs, was an independent risk factor for fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 35 publications
3
73
1
3
Order By: Relevance
“…Recently, investigators from EuroSIDA published a study on fractures (n = 496) and osteonecrosis (n = 73, 12 of whom were also included in our study), but when compared with our study, it identified quite a different set of risk factors for AVN: white race, lower nadir CD4, prior fracture/osteonecrosis, and prior AIDS [25]. We found some signal for CD4-nadir in the univariable model but not with AIDS.…”
Section: Discussioncontrasting
confidence: 47%
“…Recently, investigators from EuroSIDA published a study on fractures (n = 496) and osteonecrosis (n = 73, 12 of whom were also included in our study), but when compared with our study, it identified quite a different set of risk factors for AVN: white race, lower nadir CD4, prior fracture/osteonecrosis, and prior AIDS [25]. We found some signal for CD4-nadir in the univariable model but not with AIDS.…”
Section: Discussioncontrasting
confidence: 47%
“…64 During the first 1 to 2 years after initiation of ART, patients may lose 2% to 6% of their bone mineral density at the hip and spine. Patients who receive TDF-containing regimens have a greater initial decline in bone mineral density than those who take a TAF- or abacavir-containing regimen.…”
Section: Recommended Initial Regimensmentioning
confidence: 99%
“…Similar to CV events, the incidence of trauma fracture appears to be lower in more recent studies and in European populations. For example, the incidence of osteoporotic fracture per 1,000 person-years was reported to be 5.6 in the WIHS, 2.6 in the HIV-positive US veterans, but was only 1.35 in the Swiss HIV cohort (including only validated fractures) [27], and 1.5 in EUROSIDA [28]. …”
Section: Bone Fractures In Hiv – More Than Traditional Risk Factors Amentioning
confidence: 99%